Integrating strategic environmental assessment into power development planning in Vietnam. (Metro Manila, Philippines Asian Development Bank, 2018)
This publication presents the integration of a Strategic Environmental Assessment (SEA) in the revised Power Development Plan VII of Viet Nam.It demonstrates how incorporating an SEA into the planning process will produce plans that are based on a more thorough understanding of their implications for the economy, society, and environment of the country. Viet Nam revised Power Development Plan VII is a model of good practice in integrating an SEA in the preparation of a strategic plan for the power sector of other countries, particularly in the Greater Mekong Subregion.
Keywords: Environmental impact analysis -- Vietnam; Energy development -- Environment aspects -- Vietnam; Electronic books